Supporting the dissemination and adoption of contextualized bundled CSA/SLM practices in the Central and South Regions of Ethiopia. Activity Report. - Adimassu, Zenebe; Tibebe, Degefie; Demeke, Getamesay; Gizaw, Solomon; Kassa, Akalu; Abera, Wuletawu; Tamene, Lulseged (2025)
Over the past decade, the collaboration between the Alliance of Bioversity International and CIAT and InterAide-Ethiopia has significantly advanced integrated landscape management and biodiversity conservation in the Doyogena landscape and beyond. Building on these successes, scaling efforts were extended to the Hadiya, Kembata, and Wolaita zones through a series of interventions that integrated climate-smart agriculture (CSA) and sustainable land management (SLM) practices. A facilitation workshop held in Hawassa (16–17 July 2025) brought together 26 participants from regional and zonal institutions to assess progress and strategize for broader adoption. Key scaling approaches included the deployment of para-conservationists, the establishment of community grass multiplication sites, engagement with high-level decision makers, and the integration of physical and biological measures supported by research and by women—and reached 293 kebeles, with plans to expand to 583 kebeles and an additional 100,000 households over the next five years. CSA/SLM interventions focused on three categories: physical (e.g., soil bunds, check dams), biological (e.g., grass strips, agroforestry), and livelihood diversification (e.g., climate-resilient crops, income-generating activities, market linkages). However, key challenges—particularly open livestock grazing and limited commitment of taskforce members—remain barriers to effective scaling. The workshop emphasized the need for stronger institutional coordination, grazing management systems, and sustained community engagement to ensure long-term, scalable landscape restoration across the region.